When the liver gets stiff, the tough get moving. Issue 6 (11th February 2020) - Nguyen, Thuy‐Huong; Wardell, Rebecca; Chitturi, Shiv; Teoh, Narci; Farrell, Geoff
Abstract: Liver stiffness measurement (LSM) by FibroScan‐determined transient elastography is a noninvasive approach to estimate liver fibrosis severity. In non‐alcoholic fatty liver disease (NAFLD), advanced liver fibrosis is excluded by normal liver stiffness, but a wide range of cutoffs have been used to predict advanced liver fibrosis or cirrhosis. This may be partly because steatosis (measured by controlled attenuation parameter [CAP]) contributes to liver stiffness and also because LSM fluctuates in NAFLD. In a recent pivotal study, one‐third of patients with liver stiffness > 12.0 kPa showed reversal after 4–6 months; these cases did not have advanced liver fibrosis on biopsy. We performed serial FibroScans 6–36 months apart in 73 NAFLD patients, 38 with LSM > 10 kPa at entry. Those who lost ≥ 1 kg of weight ( n  = 31) significantly reduced liver stiffness (3.6 ± 6.1 vs 0.53 ± 4.1 kPa, P  < 0.05) and CAP score (39 ± 63 dB/m of loss vs 24 ± 65 dB/m of gain, P  < 0.05) compared with those who did not ( n  = 29). Patients who reported increased physical activity ( n  = 25) also reduced liver stiffness (3.6 ± 6 vs 0.35 ± 6 kPa) and CAP (20 ± 71 dB/m of loss vs 32 ± 71 dB/m of gain). Overall, those with improved LSM were significantly more likely to have lost weight and/or improved physical activity. These effects of lifestyle adjustments partly explain why a single measurement of 12.0 kPa is not a reliable cutoff for advanced liver fibrosis in NAFLD. In addition to repeating the study after 6–12 months, documentation of response to lifestyle advice and weight reduction should be determined before assuming any cutoff indicates advanced liver fibrosis. Despite this reservation about diagnostic accuracy, we consider that measurement of liver stiffness and CAP score serve to motivate patients to enact lifestyle modifications that can improve NAFLD severity.